The Larvacidal Activity of Ethanol Extracts of Phyllanthus acidus Leaves on The Culex quinquefasciatus Instar III/IV Larvae - Afifatun Hasanah; Bagus Hermansyah; Cholis Abrori (Faculty of Medicine, University of Jember, 2019)
Culex quinquefasciatus was one of a vector of filariasis disease caused by filarial worm infection. Mode of transmission was through mosquito bites that contain filaria worm. To overcome the problem in terms of eradicating the mosquito larvae was by searching for safe biological materials for humans and the environment, one of them was Phyllanthus acidus leaves. The purposes of this research were to know whether the ethanol extract of Phyllanthus acidus leaves have larvicidal activity on Culex quinquefasciatus instar III / IV larvae and to know the lethal concentration 50 (LC50) ethanol extract of Phyllanthus acidus leaves on Culex quinquefasciatus instar III / IV larvae within 24 hours. This study used true experimental method with post test only controlled group design with 1 positive control group (Temephos), 1 negative control group (Aquades and DMSO), and 5 treatment groups (0.0625%; 0.125%; 0.25%, 0.5% and 1% extract) respectively 20 Culex quinquefasciatus instar III/IV larvae. The result of regression test of inverse to know the effect of leaf extract of ceremai to the death of Culex quinquefasciatus larvae obtained R2=0909 which was mean the effect of ethanol extract of Phyllanthus acidus leaves to the number of the death of Culex quinquefasciatus larvae equal to 90.9%. The result of probit test obtained LC50 result of 0.189% with 95% confidence interval (0.142% -0.233%).